QRISK2 and pre-eclampsia: a postnatal study assessing cardiovascular risk. (18th April 2012) - Waring, GJ; Smith, MC; Bell, R; Brown, M; Collins, CH; Robson, SC; Waugh, JJS
Abstract : Background: Women with preeclampsia (PE) are at increased risk of cardiovascular disease(CVD) in later life. We aimed to ascertain the prevalence of markers of CVD in a cohort of women recently delivered for PE. Methods: Over 30 months all women delivered for PE(sustained BP ≥ 140/90 mmHg + proteinuria [PCR ≥30 or ≥ 0.3g/24h]) were offered postnatal review incorporating CVD risk assessment involving measurement of BP, proteinuria, fasting lipids and ten year cumulative risk of CVD event(based on QRISK2). QRISK2 scores were compared to population scores (QRISK2/population risk) to give relative risk (RR). Findings: 100 of 218 women offered an appointment attended 8-10 weeks after delivery. Mean (SD) age was 30.6(5.2) years; 80% were primigravida, 88% white, 36% delivered preterm, 59% had a family history of CVD(first degree relative), 66% had BMI >25 and 5% were current smokers. 65% had a raised total cholesterol(TC)(≥5.0mmol//L), 34% had a raised TCl/HDL ratio(≥4.0 mmol/L) and 20% had raised triglycerides(≥1.7 mmol/L). 23% were taking BP medication and 25% were found to be hypertensive. 26% met diagnostic criteria for the metabolic syndrome.1 Median cohort QRISK2 score was 0.4%(IQR 0.2-0.8), median control QRISK2 score was 0.2%(IQR 0.2-0.4). Median RR was 1.5(IQR 1.0-2.5) compared to age-matched population risk. Interpretation: A high proportion of women screened 8-10 weeks after PE have risk factors for CVD. Based on the QRISK2 CVD prediction model a significant number of this group of women have at least a 2 fold higher than expected risk of developing CVD in the next 10 years.